Accessing surgical care for esophageal cancer: patient travel patterns to reach higher volume center. Issue 7 (25th February 2020) - Diaz, Adrian; Burns, Sarah; D'Souza, Desmond; Kneuertz, Peter; Merritt, Robert; Perry, Kyle; Pawlik, Timothy M
SUMMARY: While better outcomes at high-volume surgical centers have driven the regionalization of complex surgical care, access to high-volume centers often requires travel over longer distances. We sought to evaluate the travel patterns among patients undergoing esophagectomy to assess willingness of patients to travel for surgical care. The California Office of Statewide Health Planning database was used to identify patients who underwent esophagectomy between 2005 and 2016. Total distance traveled, as well as whether a patient bypassed the nearest hospital that performed esophagectomy to get to a higher volume center, was assessed. Overall 3, 269 individuals underwent an esophagectomy for cancer in 154 hospitals; only five hospitals were high volume according to Leapfrog standards. Median travel time to a hospital that performed esophagectomy was 26 minutes (IQR: 13.1–50.7). The overwhelming majority of patients (85%) bypassed the nearest providing hospital to seek care at a destination hospital. Among patients who bypassed a closer hospital, only 36% went to a high-volume hospital. Of the 2, 248 patients who underwent esophagectomy at a low-volume center, 1, 491 patients had bypassed a high-volume hospital. Of the remaining 757 patients who did not bypass a high-volume hospital, half of the individuals would have needed to travel less than an additional hour to reach a high-volume center. Nearly two-thirds of patients undergoing an esophagectomy for cancer received care at a low-volume center; 85% of patients either bypassed a high-volume hospital or would have needed to travel less than an additional hour to reach a high-volume center.